Characterization of Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) Binding Proteins - Zhu, D (2018)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a potent intracellular second messenger capable of inducing calcium release from acidic organelles and is responsible for many important physiological activities. It has been recognized that an intermediate protein is required for NAADP to mediate its calcium-mobilizing effect through two-pore channels (TPCs). However, the identity of the intermediate NAADP binding protein remains unknown. This thesis aims to identify the elusive NAADP binding proteins to further elucidate the molecular mechanism of NAADP signalling pathway. The first part of this thesis describes the characterization of NAADP binding protein using a chemistry approach, which includes crosslinking study in mouse embryonic fibroblasts (MEFs) and affinity isolation of binding protein via a NAADP affinity column. Crosslinking introduced significant interference to NAADP binding in MEFs. Radioligand binding assays revealed that NAADP binding in MEFs were predominantly in the membrane fraction and no high affinity binding site was detected. Affinity isolation of binding proteins by NAADP affinity columns was carried out using mouse liver cytosol. However, no high-affinity binding protein was isolated through this approach. The second part of this thesis describes the identification of NAADP binding proteins via a combination of techniques including protein chromatography, photoaffinity labelling, mass spectrometry, virtual screen and label-free ligand binding assays. A sequential chromatography was conceived and optimized, which achieved a more than 2300-fold enrichment of high-affinity binding proteins. Photoaffinity labelling of the enriched fractions by [32P]-5-azido-NAADP revealed a 27 kDa band in SDS-PAGE gel. Subsequent mass spectrometry analysis generated a list of 35 candidates. Virtual screening of candidates by AutoDock Vina and CLC Drug Discovery Workbench predicted Carbonyl Reductase 1 (CBR1), Thiopurine S-Methyltransferase (TPMT) and Cytochrome b5 Reductase 3 (CYB5R3) as promising NAADP binding protein candidates. Further experimental validation by bio-layer interferometry (BLI) and microscale thermophoresis (MST) confirmed that TPMT and CBR1 are NAADP binding proteins. CBR1 binds NAADP and NADP with similar affinities. On the other hand, TPMT showed higher affinity and high selectivity to NAADP as no binding of NADP was observed. The identification of NAADP binding protein suggests new possibility of NAADP functionality and may provide new insights into the mechanism of action of NAADP signalling pathways.